Glacier area shrinkage in China and its climatic background during the past half century - 张明军 王圣杰 李忠勤 王飞腾 (Journal of geographical sciences, 2012)
Based on the glacier area variation records in the typical regions of China moni-tored by remote sensing, as well as the meteorological data of air temperature and precipitation from 139 stations and the 0℃ isotherm height from 28 stations, the glacier area shrinkage in China and its climatic background in the past half century was discussed. The initial glacier area calculated in this study was 23,982 km2 in the 1960s/1970s, but the present area was only 21,893 km2 in the 2000s. The area-weighted shrinking rate of glacier was 10.1%, and the interpolated annual percentage of area changes （APAC） of glacier was 0.3% a–1 since 1960. The high APAC was found at the Ili River Basin and the Junggar Interior Basin around the Tianshan Mountains, the Ob River Basin around the Altay Mountains, the Hexi Interior Basin around the Qilian Mountains, etc. The retreat of glacier was affected by the climatic background, and the influence on glacier of the slight-increased precipitation was counteracted by the significant warming in summer.